Pengembangan Game Labu Siswa Kelas VII - Dini Hapsari; Agus Wedi; Sulthoni Sulthoni (Universitas Negeri Malang, 2021)
Earth layer game (Game LABU) is modifying science learning media into a fun game to increase student motivation. The teaching and learning media developed is the LABU game for Natural Science (IPA) subjects. The aim of developing the LABU game is to produce a LABU multimedia game product for grade VII students that is feasible to be applied in learning. This study uses the Lee & Owens method. Evaluation of LABU multimedia game products by several media experts and material experts. The LABU game product trial involved 6 grade VII students of SMPN 2 Gurah. In conclusion, product review data received positive responses in the positive category.AbstrakGame lapisan bumi (Game LABU) yaitu memodifikasi media belajar IPA menjadi sebuah permainan menyenangkan untuk meningkatkan motivasi belajar siswa. Media belajar mengajar yang dikembangkan yaitu game LABU mata pelajaran Ilmu Pengetahuan Alam (IPA). Tujuan pengembangan game LABU yaitu untuk menghasilkan produk multimedia game LABU siswa kelas VII yang layak diterapkan didalam pembelajaran. Penelitian ini menggunakan metode Lee & Owens. Penilaian terhadap produk multimedia game LABU yaitu oleh beberapa ahli media dan ahli materi. Uji coba produk game LABU melibatkan 6 siswa kelas VII SMPN 2 Gurah. Simpulan data hasil review produk memperoleh tanggapan positif dalam kategori positif.